Complications associated with myocardial bridging in four children without underlying cardiac disease: a case series. (2nd October 2021) - Brancato, Federica; Rigante, Donato; Piastra, Marco; Gambacorta, Alessandro; Aurilia, Claudia; De Rosa, Gabriella
ABSTRACT: Background: Myocardial bridging is largely considered to be a benign, symptomless congenital anomaly of the coronary arteries in which the intramyocardial coronary course is partially 'tunnelled' and leads to vessel compression during ventricular systole. There are few data regarding children. Objective: To report on myocardial bridging observed in children seeking medical help in the paediatric emergency room. Case presentation: A series of four children aged 6–13 years with symptomatic myocardial bridging but no other underlying cardiac abnormalities is reported. They were admitted to the paediatric emergency department during 2013–2016, three with chest pain after physical activity and one with septic shock. Results: Heart computed tomography scan in the first three demonstrated myocardial bridging of the left anterior descendent coronary artery's branches; their 2-year follow-up was uneventful. The fourth patient presented with ventricular fibrillation 24 hours after admission and at autopsy there was an intramyocardial tract 4 cm long on the left anterior descendent coronary artery. Conclusions: This case series demonstrates that myocardial bridging can be symptomatic in children with no underlying cardiac disorders and should be included in the differential diagnosis of exertional chest pain and/or arrhythmias. Abbreviations: CRP, C-reactive protein; CT, computed tomography; D1, diagonal 1 artery; ECG, electrocardiogram; ED, emergency department; KD, Kawasaki disease; LAD, left anterior descending coronary artery; MB, myocardial bridging; RI, ramus intermedius artery; TN, troponin.